Analisis Supply Chain Management dan Enterprise Resource Planning pada Perusahaan H&M - Angelino, Kevin; Jenny; Lina; Hendri Wijaya; Tondy; Fendy Cuandra (Humantech : Jurnal Ilmiah Multidisiplin Indonesia, 2022)
The development of world technology is very fast, so people can very easily communicate in any way without considering distance and time. One way to get it all is to have the internet. Over time the use of the internet is growing day by day. This has a positive impact on all groups of people because they can access it through Internet Banking. Apart from the positive side of the internet, it turns out that there are also negative impacts from the internet on people's daily lives, such as credit card burglary through the Internet Banking system, so the public or customers must be cautious in guarding against credit card burglaries carried out by irresponsible persons, on the other hand, Indonesian banks have several regulations in place to protect their customers, especially in the use of credit cards. For example, customers can sue criminally, where customers can report the bank as a credit card provider to the authorities on the suspicion that the bank has distributed customer personal data. At the same time, civilly, they can claim compensation from the bank. The number of cases related to the leakage/misuse of customer personal data has become a central issue in the banking industry. This problem is crucial because it is related to customer security and trust in the existence of banking institutions, so it needs to be addressed as much as possible.